An African perspective to biodiversity conservation in the twenty-first century - (:unkn) unknown (My University, 2025)
Africa boasts high biodiversity while also being home to some of the largest and fastest-growing human populations. Although the current environmental footprint of Africa is low compared to other continents, the population of Africa is estimated at around 1.5 billion inhabitants, representing nearly 18% of the world’s total population. Consequently, Africa’s rich biodiversity is under threat, yet only 19% of the landscape and 17% of the seascape are under any form of protection. To effectively address this issue and align with the Convention on Biological Diversity’s ambitious ‘30 by 30’ goal, which seeks to protect 30% of the world’s land and oceans by 2030, substantial funding and conservation measures are urgently required. In response to this critical challenge, as scientists and conservationists working in Africa, we propose five recommendations for future directions aimed at enhancing biodiversity conservation for the betterment of African society: (i) accelerate data collection, data sharing and analytics for informed policy and decision-making; (ii) innovate education and capacity building for future generations; (iii) enhance and expand protected areas, ecological networks and foundational legal frameworks; (iv) unlock creative funding channels for cutting-edge conservation initiatives; and (v) integrate indigenous and local knowledge into forward-thinking conservation strategies. By implementing these recommendations, we believe Africa can make significant strides towards preserving its unique biodiversity, while fostering a healthier society, and contributing to global conservation efforts. This article is part of the discussion meeting issue ‘Bending the curve towards nature recovery: building on Georgina Mace's legacy for a biodiverse future’.
Keywords: African Research